Determination of the Impact of Electronic Health Information Systems upon Medical, Medical Backing and Administrative Decisions in Al-Kindy Teaching Hospital - jassim, basima (Iraqi National Journal of Nursing Specialties, 2015)
Objective(s): To determine the impact of the electronic Health Information Systems upon medical, medical Backing and administrativedecisions in Al-Kindy Teaching Hospital. Methodology: A descriptive analytical design is employed through the period of June 14th 2015 to August 15th 2015. A purposive "non- probability" sample of (50) subject is selected. The sample is comprised of (25) medical and medical backing staff and (25) administrative staff who are all involved in the process of decision making in Al-Kindy Teaching Hospital. A self-report questionnaire, of (68) item, is adopted and developed for the purpose of the present study and it is consisted of (6) subscales that measure the phenomenon underlying the study. The questionnaire is rated and scored on 5-level type Likert scale of strongly agree= 5, agree=4, uncertain= 3, disagree=2, and strongly disagree=1. Internal consistency reliability is determined for the questionnaire through split-half technique and computation of Cronbach’s AlphaCorrelation Coefficient of (r= 0.96) for the internal scale. Content validity for the questionnaire is determined through panel of (9) experts in the fields of medicine, medical backing, and management. Data are collected through the use of the self-report questionnaire as mean of data collection. Data are analyzed through the application of the descriptive statistical data analysis approach of frequencies, percentages, and computation of total scores, mean of scores and Pearson Correlation Coefficient. Results:The present study indicates that the Electronic Health Information Systems have great impact upon decisions of medical, medical backing and administrative staff. The higher the level of these staff characteristics of years of employment, place of work and education, the greater the impact of the Electronic Health Information Systems. Recommendations:The present study recommends that establishment of a nationwide network for Electronic Health Information Systems by which health care organizations can be connected. Increase all medical, medical backing and administrative staff awareness toward the benefits of using the Electronic Health Information Systems. Further research can be conducted with large sample size, different settings and various characteristics.